The Social Network Learning Cloud: Architectural Education for the 21st Century. (September 2014) - Schnabel, Marc Aurel; Ham, Jeremy J
In less than a decade, architectural education has, in some ways, significantly evolved. The advent of computation has not so much triggered the change, but Social Networks (SN) have ignited a novel way of learning, interaction and knowledge construction. SN enable learners to engage with friends, tutors, professionals and peers, form the base for learning resources, allow students to make their voices heard, to listen to other views and much more. They offer a more authentic, inter-professional and integrated problem based, Just-in-Time (JIT), Just-in-Place (JIP) learning. Online SN work in close association with offline SN to form a blended social learning realm – the Social Network Learning Cloud (SNLC) – that greatly enables and enhances students' learning in a far more influential way than any other learning means, resources or methods do. This paper presents a SNLC for architectural education that provides opportunities for linking the academic Learning Management Systems (LMS) with private or professional SN such that it enhances the learning experience and deepens the knowledge of the students. The paper proposes ways of utilising SNLC in other learning and teaching areas of the curriculum and concludes with directions of how SNLC then may be employed in professional settings.